Rendimento de massa de matéria seca e relação c/n da aveia preta em função do lodo de esgoto e adubação nitrogenada - Lobo, Thomaz Figueiredo [UNESP]; Grassi Filho, Helio [UNESP]; Bull, Leonardo Theodoro [UNESP] (My University, 2012)
The final display of sewage sludge has been characterized as one of the most relevant environmental problems in the cities; it daily increases in both developed and developing countries, resulting in larger collection networks and increased treatment levels. The aim of this study was to verify the effect of mineral N and sewage sludge on dry matter yield and C/N ratio in black oat. The experiment was conducted in São Manuel Experimental Farm, belonging to the Faculty Agronomic Sciences, Unesp, Botucatu. The adopted experimental design was in randomized blocks constituted of 6 treatments and 5 replicates, as follows: T0 – without nitrogen fertilization; T1 – 70 kg ha-1 of the N mineral; T2 – 35 kg ha-1 of the N from sewage sludge and 35 kg ha-1 of the N in the mineral form; T3 – 70 kg ha-1 of the N from sewage sludge; T4 – 105 kg ha-1 of the N from sewage sludge;-T5 – 140 kg ha-1 of the N from sewage sludge. The parameters evaluated were dry matter acumulation and C/N ratio; with collections made at 60, 75, 90, 105 and 120 days after sowing. Increasing the dose of sewage sludge provided increment in dry matter yield in oat. The N provided a lawoer C/N ratio in plant oats.
Yield of dry matter and c/n ratio of oats as a functional of sewage sludge and nitrogen
Keywords: Avena strgigosa; N mineralization; Organic matter and plant nutrition